Fresh-frozen human bone allograft in vertical ridge augmentation: clinical and tomographic evaluation of bone formation and resorption - Scavone Macedo, Luis Guilherme [UNESP]; Mazzucchelli-Cosmo, Luiz Antonio; Macedo, Nelson Luiz [UNESP]; Ferreira Monteiro, Adriana Socorro [UNESP]; Sendyk, Wilson Roberto (Springer, 2012)
The aim of the current study is to evaluate fresh-frozen human bone allografts (FHBAs) used in vertical ridge augmentation clinically and by computed tomography, and to analyze the resulting bone formation and graft resorption. Sixteen FHBAs were grafted in the maxillae and mandibles of 9 patients. The FHBAs, which were provided by the Musculoskeletal Tissue Bank of Marilia Hospital (Unioss), were frozen at -80A degrees C. After 7 months, dental implants were placed and bone parameters were evaluated. Vertical bone formation was measured by computerized tomography before (T0) and at 7 months (T1) after the surgical procedure. Bone graft resorption was measured clinically from a landmark screw head using a periodontal probe. The results were analyzed by Student's t-test. Significant differences existed in the bone formation values at T0 and T1, with an average change of 4.03 +/- A 1.69 mm. Bone graft resorption values were 1.0 +/- A 0.82 mm (20%). Implants were placed with varying insertion torque values (35-45 Ncm), and achieved primary stability. This study demonstrates that FHBAs promote satisfactory vertical bone formation with a low resorption rates, good density, and primary implant stability.
Keywords: Dental implants; Transplantation; Allograft; Bone bank; Bone; Fresh frozen graft